Exploring Cu-Ge alloys as filler materials for high vacuum brazing application of W and CuCrZr. (December 2022) - de Prado, J.; Sánchez, M.; Izaguirre, I.; Swan, D.; Ureña, A.
Abstract: Cu-Ge system was evaluated for its application as a filler material in W-CuCrZr joints proposed as heat sink components of the future fusion power plants. The selected compositions were rich in Cu, with the aim of retaining the ductility that characterizes copper metal. Three compositions (Cu-13.5Ge, Cu-19.5Ge and Cu-33.2Ge) and two manufacturing routes (flexible and rigid tapes) were evaluated and characterized thermally, microstructurally and mechanically. The brazing temperature decreased as the Ge content increased, giving rise to less base material thermal affectation. The microstructure was dominated by several peritectic reactions that hinder the solid state diffusion control, and three main phases (Cu solid solution, ε and ζ) were detected both in the solidified filler drop and in the joint braze. In addition, the rigid filler manufacturing route seemed to produce more continuous joints due to its more homogeneous composition. The mechanical properties indicated that both lower and richer Ge compositions gave rise to joints with higher strength. Graphical Abstract: ga1